The interaction features of the multi-level retaining walls with soil mass = Analiza właściwości interakcji pomiędzy wielopoziomowymi murami oporowymi a gruntem - Boyko, Igor; Skochko, Ludmila; Zhuk, Veronica (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The interaction features of multi-level retaining walls with soil base were researched by changing their geometric parameters and locality at the plan. During excavation of deep foundation pits it is important to choose the type of constructions which influences on the horizontal displacements.
Keywords: multi level retaining wall; elastic-plastic model; in situ test; geodetic monitoring; mur oporowy wielopoziomowy; model sprężysto-plastyczny; test in-situ; monitorowanie geodezyjne